Inclusivity and Diversity in ELT Material: Critical Textual Analysis as a Pedagogical Tool - Sreemali Herath (The Open University of Sri Lanka, 2020)
Promoting equity and diversity within the classroom and the wider school culture is often overlooked in most educational contexts. The focus on student diversity is important as teachers need to be able to use classroom instruction and communication to make their classes inclusive for all learners. Yet, how can classrooms be inclusive and safe learning environments that offer all students the space to grow and reach their full potential? How can teachers design and deliver lessons so that all learners feel they belong to the school community? How can teachers help their learners appropriate pedagogical content on their own terms? These are concerns this paper attempts to answer. Focusing on English Language Teaching (ELT) material, it discusses how educational discoureses in textbooks reproduce inequalities that exist outside of the classroom and how critical discourse analysis (CDA) can be used to deconstructs texts in order to explore ways in which they relate to broader sociopolitical contexts. Drawing on selected tenets of CDA, this study discusses how they can be used as an analytical tool to critically examine the relations between discourse, power, dominance, and social inequality present in textbooks and identify ways in which educators can adapt and appropriate material in ways that help their learners to build on the cultural and linguistic capital they bring with them to the classroom.